Infant disorganized attachment: Clarifying levels of analysis. (October 2017) - Duschinsky, Robbie; Solomon, Judith
Lack of clarity regarding the infant disorganized attachment classification has caused confusion in the clinical, forensic, and research contexts in which it is used. This article offers distinctions to clarify the concept with the goal of increasing understanding and identifying potential misapplications. In particular, attention is drawn to the fact that there are many indices used to code "disorganized attachment, " and that so far they have been validated as a set rather than individually; and it is noted that the construct validation of disorganization in naturalistic settings is partially finished. Clinicians and social workers should be cautious in their interpretations of such behavior.